Diagnostic and prognostic value of C-reactive protein in infective endocarditis - M. A. Gurevich; S. Ya. Tazina; T. G. Kabanova (Российский кардиологический журнал, 2006)
The number of patients with infective endocarditis (IE) has been growing in the recent years, justifying further studies on diagnostic IE criteria. The article is devoted to C-reactive protein role (CRP) in IE diagnostics. It has been demonstrated that high CRP level is a marker of serious infective and toxic disease manifestations, associated with primary IE, severe myocardial damage, right heart chamber IE. Dynamic CRP measurement helps to control therapy effectiveness and assess clinical prognosis in IE patients.